2022
DOI: 10.3390/ma15217469
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mechanical Properties of Composites Reinforced with Technical Embroidery, UD and Woven Fabric Made of Flax Fibers

Abstract: The main purpose of the article is to present the possibilities of producing composite reinforcement with the use of a computer embroidery machine. The study below presents the results of strength tests of composites containing technical embroidery, woven fabric, and UD fabric as the reinforcement. Each of the samples was made of the same material—flax roving. The samples differed from each other in the arrangement of layers in the reinforcement. The composites were made using the infusion method with epoxy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Again, similarly to the dry fibers, the carbon-BB stiffness is around three times larger than the glassor basalt-BB. As observed by other studies [7,24], the behavior of the flax fibers, in terms of stiffness, is close to both basalt and glass fibers. It is important to mention, that the average f vc obtained in the specimens is below the intended one.…”
Section: Specific Stiffness and Specific Stiffness Carbon Footprintsupporting
confidence: 85%
See 1 more Smart Citation
“…Again, similarly to the dry fibers, the carbon-BB stiffness is around three times larger than the glassor basalt-BB. As observed by other studies [7,24], the behavior of the flax fibers, in terms of stiffness, is close to both basalt and glass fibers. It is important to mention, that the average f vc obtained in the specimens is below the intended one.…”
Section: Specific Stiffness and Specific Stiffness Carbon Footprintsupporting
confidence: 85%
“…Almeida Jr. et al [ 23 ] have improved an already optimized component and results have shown that outstanding mechanical behavior can be obtained by TFP-made components even when compared with other high-performance composites. Poniecka et al [ 24 ] have used the process to evaluate the mechanical properties of different configurations of flax fibers—from UD to woven fabric—considering different TFP parameters. Their results have shown that strength values were higher in UD TFP samples when compared to conventional UD-reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…As proven in previous studies, the use of technical embroidery for the production of composite reinforcements improves strength of composites, compared to ones containing woven fabric as reinforcement. [19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been successfully used in the fields of manufacturing antennas, coils of unilateral nuclear magnetic resonance systems, etc. [22][23][24][25] Computer embroidery technology can stack the conductive sewing thread into FSS patterns, and can also form corresponding patterns according to the designed shape and size to produce electromagnetic wave frequency selective transparent textiles. Therefore, FSFs can be prepared by increasing the conductivity of the embroidery yarn and using periodic embroidery patterns.…”
Section: Introductionmentioning
confidence: 99%